Nurturing care in the first 10 years of life: Results from a Vietnamese longitudinal study - Tran, Lan Mai; Stein, Aryeh D.; Nguyen, Phuong Hong; Young, Melissa F.; Ramakrishnan, Usha (Wiley, 2025)
Nurturing care (NC) is essential for children to meet their optimal development potential. However, the various NC dimensions and their patterns from preconception through adolescence have not been comprehensively documented. This study explored five NC dimensions (health, nutrition, safety/security, learning, and relationships) using prospectively collected data from 1040 mother–child dyads in a birth cohort conducted in Vietnam from 2011 to 2023. We described distributions of age‐specific variables of the NC dimensions from preconception through ages 2, 6, and 10 years, and generated scaled scores that ranged from 0 to 1. Mean scores varied across dimensions and life stages (range: 0.45–0.83). The scores were 0.1–0.2 points higher among mothers with higher schooling levels. Smaller differences (0.03–0.06 points) in scores were also observed between ethnicities, but no significant difference was observed between boys and girls. We observed positive correlations among most of the five dimensions within each study period (r range: 0.03–0.38). The variation of NC dimensions across different time points indicates a need to measure NC across life stages. Our findings demonstrate important gaps in gaining full achievement in NC from preconception through age 10 years.